Alice in Wonderland - Collins, Joan; Carroll, Lewis Frankland, David Mercer, Jonathan (Ladybird Loughborough, 1994)
"When alice follows a white rabbit in a waisecoat down a hole, she finds herself in a mixed-up world where nothing is as she expects it to be, and anything can happen! Alice meets a pipe-smoking caterpillar, a grinning cat, a Mad Hunter and the formidable Queen of hearts" --Back cover